Comparative Analysis of Academic Journals on Health - Nazmi Kozak (Türk Kütüphaneciliği)
This study aims to investigate if there are any differences in the practices of publishing and manuscript review among the three categories of journals on the subjects of health, social and pure sciences being published in Turkey. The discussion of the findings is based on an empirical investigation carried out among the editor-in-chiefs of 323 academic journals. Data were analysed using SPSS statistical programme. The assessment of findings suggests that there appear to be significant differences in some practices and procedures among all the three categories of academic journals. The most significant differences appear in such practices and procedures as manuscript review and refereeing policy.